DEVELOPMENT OF SELF-CONCEPT OF PRIMARY SCHOOL AGE CHILDREN WITH CARDIOVASCULAR DISEASES - Onyshchenko, Vitaliy (PSYCHOLOGICAL JOURNAL, 2020)
The article raises the question of the development of self-concept of primary school children having cardiovascular diseases. The theoretical approaches of national and foreign scientists studying self-concept are reviewed, factors affecting its formation at primary school age are considered. Special attention is paid to influence of comprehensive school with medical care provision teaching children having cardiovascular diseases. We indicate that the primary school age is one of most important periods for self-concept development and formation, since schoolchildren develop and expand the sphere of their Self. First of all, the position of "I" in relation to society is formed, mental methods are formed (thinking, the ability to analyze, generalize, compare are developed), and certain personal properties are also formed. The psychological characteristics of children with congenital cardiovascular diseases, if they are not accompanied by secondary diseases, do not differ from the psychological characteristics of healthy primary school age children, however, the performed empirical study showed differences for such indicators of the self-concept as Self-real, Self-ideal, self-esteem and its differentiation. This result can be associated with favorable conditions for children’s education at comprehensive school with medical care provision. After the interpretation of the used research methods, we have concluded that primary school age children with cardiovascular diseases studied in comprehensive school with medical care provision, in comparison with healthy children of the same age, have adequate self-esteem of an average level, but healthy children usually have increased self-esteem. Children with cardiovascular diseases have normal, adequate self-esteem and adequate self-concept, but slightly increased anxiety. Research results can be used in work with children having cardiovascular disease and by practical psychologists working with primary school age children.